INFORMATION PROFESSIONAL AT THE POINT OF CARE: CLINICAL LIBRARIAN SERVICE IN NEUROCRITICAL CARE - Santos, Mark Anthony A.; Mariano, Geraldine Siena L. (Journal of Philippine Librarianship, 2015)
This paper documented the first clinical librarian service initiated in the Philippines. The role and experiences of the clinical librarian integrated in a multidisciplinary neurocritical care clinical team of a tertiary teaching hospital, and its effectiveness during the 6-month pilot was discussed. An evaluation of the pilot study was done using a questionnaire survey.